AN EXAMINATION OF INTELLECTUAL PROPERTY CONTRACTS FROM AN ISLAMIC VIEWPOINT - Rohaya, Nizla (Lex Jurnalica, 2024)
The examination of Intellectual Property Contracts from an Islamic viewpoint sheds light on the intricate interplay between legal structures, economic factors, and ethical principles. This study delves into the historical evolution of Intellectual Property Rights (IPR) legislation in Indonesia, emphasizing the nation's commitment to fostering innovation, attracting foreign investment, and safeguarding creators' and innovators' rights. The concept of waqf (endowment) of IPR within Islamic law underscores the potential for utilizing intellectual property for societal benefit, emphasizing ethical considerations. Additionally, the application of Islamic treaty law in IPR contracts underscores the importance of fairness, transparency, and mutual benefit in business transactions. Challenges such as piracy, counterfeiting, and online infringement pose threats to effective IPR protection in Indonesia, necessitating robust enforcement efforts and the application of Islamic economic business ethics. By understanding the social and economic impacts of IPR contracts within an Islamic framework, policymakers and stakeholders can develop strategies that promote innovation, creativity, and economic growth while upholding ethical standards and legal principles. The study advocates for enhancing IPR protection, investing in enforcement mechanisms, and leveraging Islamic law to address digital age challenges, fostering an environment conducive to innovation, respecting intellectual property rights, and promoting ethical business practices for economic development and social welfare.